A model of housing stock for Canada - David Dupuis; Yi Zheng (Bank of Canada, 2010)
Using an error-correction model (ECM) framework, the authors attempt to quantify the degree of disequilibrium in Canadian housing stock over the period 1961-2008 for the national aggregate and over 1981-2008 for the provinces. They find that, based on quarterly data, the level of housing stock in the long run is associated with population, real per capita disposable income, and real house prices. Population growth (net migration, particularly for the western provinces) is also an important determinant of the short-run dynamics of housing stock, after controlling for serial correlation in the dependent variable. Real mortgage rates, consumer confidence, and a number of other variables identified in the literature are found to play a small role in the short run. The authors' model suggests that the Canadian housing stock was 2 per cent above its equilibrium level at the end of 2008. There was likely overbuilding, to varying degrees, in Saskatchewan, New Brunswick, British Columbia, Ontario, and Quebec.
Keywords: E21; J00; 330; Domestic demand and components; Immobilienmarkt; Wohnungsversorgung; Bevölkerungsentwicklung; Internationale Wanderung; Kanada